Echolocating bats sacrifice binaural localization cues for target-focused hearing during high-speed foraging - Felix T. Häfele; Danuta M. Wisniewska; Karsten K. Vesterholm; Lasse Jakobsen (Proceedings of the National Academy of Sciences, 2026)
Accurate sound localization is critical to navigation and foraging in echolocating animals. During both passive listening and active echolocation, bats are thought to rely solely on interaural level differences (ILDs) between the two ears, attaining very large ILDs by orienting their outer ears apart. However, detecting weak prey echoes during high-speed foraging should instead favor target-focused pinnae that maximize sonar range and reduce clutter interference. Therefore, we propose that flying bats orient their pinnae toward prey. We test this hypothesis using a unique wind tunnel and by employing deep-learning-facilitated high-speed stereo photogrammetry and show that freely flying bats indeed orient their pinnae forward, directly on target. This produces large spatial overlap between each ear’s receiving beams, markedly reducing ILDs, and rejects the hypothesis that bats rely solely on ILDs for localization in flight. Instead, bats achieve a highly directional acoustic field of view through coordinated alignment of the emitted and received sonar beams, which amplifies the central acoustic axis and attenuates off-axis echoes. Parallel to visual object tracking, flying bats likely prioritize signal-to-noise ratio, trading off large ILDs for clutter-filtering and sonar range, which allows them to use very weak echoes and simplify their self-generated auditory scene. We hypothesize that this highly directional acoustic field of view aids in localization, potentially in combination with interaural time differences, in the absence of large ILDs. This envisions an inherently simplified acoustic scene that better accounts for how bats hunt efficiently in complex environments.